Apparent Diffusion Coefficient Mapping of the Normal Parotid Gland and Parotid Involvement in Patients with Systemic Connective Tissue Disorders - Patel, Rahul R.; Carlos, Ruth C.; Midia, Mehran; Mukherji, Suresh K. (American Journal of Neuroradiology, 2004)
PURPOSE: We hypothesized that a difference in restricted diffusion would exist in patients with connective tissue disorders (CTD) as compared with those without CTD. Our purpose was to determine whether the apparent diffusion coefficient (ADC) measurement could be used to identify parotid abnormalities in patients with CTD.METHODS: One neuroradiologist, who was unaware of patient histories, retrospectively measured the ADC values for the parotid glands in 121 patients who underwent clinically indicated brain MR imaging in which the parotid glands were sufficiently depicted. Regions of interest were obtained from both the left and right parotid glands. After the medical records were reviewed and exclusion criteria were used, 90 non-CTD and seven CTD patients (systemic lupus erythematosus = 5; discoid lupus erythematosus = 1; Sjögren syndrome = 1) remained. The two groups were then compared. Statistical analysis consisted of Wilcoxon sign rank and Mann-Whitney tests.RESULTS: The combined mean ADC for both parotid glands in 90 healthy patients was 0.50 extpm 0.28 exttimes 10-3 mm2/s (95% CI, 0.44 exttimes 10-3, 0.56 exttimes 10-3). The combined mean ADC for both parotid glands in the seven CTD patients was 0.96 extpm 0.24 exttimes 10-3 mm2/s (95% CI, 0.79 exttimes 10-3, 1.14 exttimes 10-3). The mean ADC for the CTD patients’ parotid glands was significantly higher than that of the non-CTD patients (P = .0001), which suggests there is less restricted diffusion in parotid glands affected by CTD when compared with normal parotid glands.CONCLUSION: These results suggest that ADCs may be used to detect parotid abnormalities in patients with CTD that are not identified by standard imaging. Although preliminary, the results indicate a potential role for ADC mapping in detection of subclinical parotid disease.